Colloquial language used in speaking classes by the English major sudents of Foreign Language Faculty - Thai Nguyen University= Ngôn ngữ thông tục được sử dụng trong các tiết học nói của sinh viên chuyên ngành tiếng Anh Khoa Ngoại Ngữ - Đại học Thái Nguyê - Nguyễn, Dương Hà (University of Foreign Languages and International studies, 2017)
50 p. + CD-ROM